Designing multi-agent gameplay - Teslyuk, V.; Lozunskyi, A.; Teslyuk, T.; Denysyuk, P. (Lublin, 2018)
There is an attention shift within the gaming industry toward the more natural behavior of nonplaying characters. The first part of this paper says about the main concepts of agent and multi-agent systems. The main part of this paper describes the main problem in any multi-agent system, agent communication. Then we write about main concepts of designing multi-agent gameplay and describes own developed MAS game simulator.
Keywords: MAS; agents; ACM; JADE; gamebot